2001
DOI: 10.1128/mcb.21.16.5306-5311.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Mouse Kinesin Motor Kif3C

Abstract: Members of the kinesin II family are thought to play essential roles in many types of intracellular transport. One distinguishing feature of kinesin II is that it generally contains two different motor subunits from the Kif3 family. Three Kif3 family members (Kif3A, Kif3B, and Kif3C) have been identified and characterized in mice. Intracellular localization and biochemical studies previously suggested that Kif3C is an anterograde motor involved in anterograde axonal transport. To understand the in vivo functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…The results of our analysis are in agreement with reports that kif3c KO mice are viable and do not display photoreceptor defects (22,23). However, a redundancy of kif3c/kif3b function in photoreceptor cells is surprising in light of previous reports that kif3c is primarily expressed in ganglion cell axons and in amacrine cells (9,10).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results of our analysis are in agreement with reports that kif3c KO mice are viable and do not display photoreceptor defects (22,23). However, a redundancy of kif3c/kif3b function in photoreceptor cells is surprising in light of previous reports that kif3c is primarily expressed in ganglion cell axons and in amacrine cells (9,10).…”
Section: Discussionsupporting
confidence: 82%
“…The same studies reported that Kif3c is structurally related to Kif3b and, similar to Kif3b, associates with Kif3a, which suggests that Kif3b and Kif3c proteins may function redundantly as alternative binding partners of Kif3a. Although redundancy of kif3b and kif3c function has been hypothesized (9,22), to our knowledge, this is the first study to demonstrate that it actually exists. In the ear, this redundancy is limited to cilia in a subset of auditory hair cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The KIF3 KRPs were also detected in testis (24); KIF3A and KIF3B form heterodimers that function as microtubule-based (ϩ)-end transporters of membranous organelles (25). A KIF3C knockout mouse is viable and apparently normal (26). Finally, kinesin II, a member of the KIF3 family, is expressed in developing rat, sea urchin, and sand dollar sperm tails (27,28).…”
mentioning
confidence: 99%